Non-Netonian flows over an oscillating plate with variable suction - Hayat, T.; Abbas, Q.; Khan, M.; Siddiqui, A.M. (Archives of Mechanics, 2003)
The flow of second order fluid due to an oscillating infinite plate in the presence of a transverse magnetic field for two forms of time-depend suction are considered. The analytical solution of the governing boundary value problems are obtained. It is found that an external magnetic field and normal stress coefficient on the flow has opposite effects.